The first appearance of Hystrix (Rodentia, Mammalia) in Portugal, last Interglacial, Gruta da Figueira Brava (Setúbal) - Cardoso, João Luís (2021)
A fossil remain of porcupine, a large-sized rodent hitherto unknown in Portugal, was identified during the 2010-13 excavation of the Last Interglacial deposit of Figueira Brava cave. The specimen is a left hemimandible retaining the PM/4 to M/2 series but lacking the incisor and the M/3. Based on the analysis of its morphological and odontometric features, we assign the fossil to Hystrix cristata (Linnaeus, 1758). Nowadays, H. cristata is found in Africa as well as, recently introduced, in Italy. Most Late Pleistocene occurrences of the genus are assigned to the species Hystrix (Acanthion) vinogradovi but, as demonstrated by the fossil discovered in Figueira Brava, H. cristata once existed in Europe.